Programa “GAQUI” y su influencia en el nivel de logro del aprendizaje área de Ciencia y Ambiente en niños de una Institución Educativa – Trujillo, 2017 - Gastolomendo Minchola, Kristhel Sasai (2019)
The present research work has the purpose of determining if the application of the “GAQUI” program based on direct experiences improves the levels of achievement of the learning in the area of Environmental Science of the students of first grade primary education of the IEE “Rafael Narváez Cadenillas” Trujillo 2017._x000D_ We worked with a sample of 40 students, 20 of 1 ° B as an experimental group and 20 students of 1 ° C as a control group to whom the test was applied to determine the level of learning in the area of science and environment, which was validity in the opinion of an expert and its reliability was determined through Cronbach's alpha proving to be reliable._x000D_ The procedures used were those provided by statistics, starting with the construction of tables, construction of graphs and the application of the statistical test of hypothesis testing to test the research hypothesis._x000D_ It was concluded that the application of the “GAQUI” program based on direct experiences significantly influenced the level of achievement of learning in the area of science and environment of first grade students I.E.E “Rafael Narváez Cadenillas” Trujillo 2017